5-LIPOXYGENASE INHIBITOR (ZILEUTON) PRODUCES ANTI-DEPRESSION EFFECT IN STRESS INDUCE CRS MICE MODEL - PANIGRAHI, SAPTARSHI; SURAI, SOMNATH; HONG, HAO (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The experiment aimed to find out the effectiveness of Zileuton, a 5-LOX inhibitor on depressive behavior and neuroinflammation in vivo. Method: Male ICR mice (25-30g) randomly distributed Veh+Veh, CRS+Vehicle, CRS+ZIL50, and CRS+ZIL100. Zileuton was orally given in the treatment groups for 21 days after 3 weeks of stress induce CRS model. Starting from the day 1, in CRS model, mice were immobilized 8 hr/day for consecutive 21 days to induce stress. After completing the drug administration, subjected the mice for behavioral tests, and then performed histopathological and Western Blotting. Result: Stress induces CRS model guide to the significant depressive-like behavior of the mice in behavioral tests which was united by adverse changes at the cellular/molecular level responsible for regulation of inflammatory and apoptotic processes. CRS triggered Microglial over activation in the DG of the hippocampus, which was successfully inhibited by Zileuton post-treatment at the dose of 100mg/kg than 50mg/kg. Level of TNF-α, IL- 1β, nuclear NF-κB p65, Bax, and cleaved Caspase-3 was high and Bcl-2 expression was low in the stress induce CRS -treated mice which were found to be opposite in the Zileuton (100mg/kg). However, the dose of 50mg/kg less to mimic the effects as exhibited more by the 100mg/kg dose of Zileuton. Conclusion: It can be concluded that selective 5-lipoxygenase inhibitor Zileuton can efficiently inhibit the depressive-like behavior/activity in CRS-induced depressive mouse model. The study is the first to show the role of 5-lipoxygenase enzyme in and Chronic Restraint Stress (CRS)-induced mice models of stress, anxiety or depression.